2010
DOI: 10.1152/ajpregu.00080.2010
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle inflammation is not responsible for the rapid impairment in adiponectin response with high-fat feeding in rats

Abstract: Mullen KL, Tishinsky JM, Robinson LE, Dyck DJ. Skeletal muscle inflammation is not responsible for the rapid impairment in adiponectin response with high-fat feeding in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…89 Rats given high-fat diet, which is known to increase the plasma level of free fatty acids, 13,79 developed skeletal muscle adiponectin resistance before insulin resistance 67 and the resistance could not be explained by muscle inflammation. 83 Our analysis revealed a significant correlation between BMI and plasma IL-6 (Figure 4b), but not between BMI and plasma TNFa (Figure 3b). This is consistent with the in vitro observation on adipocytes where larger adipocytes were shown to release more IL-6, but not more TNFa.…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 60%
See 1 more Smart Citation
“…89 Rats given high-fat diet, which is known to increase the plasma level of free fatty acids, 13,79 developed skeletal muscle adiponectin resistance before insulin resistance 67 and the resistance could not be explained by muscle inflammation. 83 Our analysis revealed a significant correlation between BMI and plasma IL-6 (Figure 4b), but not between BMI and plasma TNFa (Figure 3b). This is consistent with the in vitro observation on adipocytes where larger adipocytes were shown to release more IL-6, but not more TNFa.…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 60%
“…Future human studies correlating the plasma level of free fatty acids (and perhaps even the type of free fatty acids 83,84 ) and that of adiponectin are needed to further examine the potential free fatty acid-adiponectin link. Results from correlation studies performed on healthy human studies suggest that such a link exist.…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 99%
“…The concept of adiponectin resistance has been mooted and there is strong likelihood that it has important significance in certain pathologies. For example, adiponectin's metabolic effects in human skeletal muscle were blunted in tissue from obese individuals and feeding a diet high in saturated fats attenuated adiponectin-stimulated signalling and fatty acid metabolism in rodent skeletal muscle [53][54][55]. It has been proposed that adiponectin resistance precedes lipid accumulation and further metabolic disturbances induced by lipotoxicity [56].…”
Section: Adiponectin Resistancementioning
confidence: 99%
“…Indeed, strong evidence indicates that adiponectin action is reduced in skeletal muscle from obese versus lean individuals as well as in muscle from rodents fed a diet high in saturated fats [28][29][30]. Thus, it was suggested that adiponectin resistance precedes lipid accumulation and metabolic dysfunction [31].…”
Section: Adiponectin Resistance and Therapeutic Interventionmentioning
confidence: 99%